Persistent inflammation in halo nevus: when the removal is indicated. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2014)
Case report. An 11-year-old girl comes to remove a palpable nevus of the back appeared at the age of 6 years. A dermatologist had recommended removal due to post-traumatic bleeding of the nevus. In the history there were no risk factors for melanoma. Physical examination (Fig. 1, Fig. 2 at higher magnification) showed a 5 mm, palpable nevus of reddish color and tense consistency, surrounded by vitiligo halo. The dermoscopy showed telangiectases and globules (Fig. 3); the latter became more evident with the pressure which excluded the blood (Fig. 4). We diagnosed halo nevus with clinically evident inflammation. The nevus was controlled monthly for 20 months (Fig. 5, 6, 7, 8); its surface got less tense, folded, but the red color persisted albeit attenuated. Finally, we decided to remove it. The histology showed an intradermal melanocytic nevus with little lymphocytic infiltrate and extensive superficial telangiectases (Fig. 9, 10).